2020
DOI: 10.3390/app10248913
|View full text |Cite
|
Sign up to set email alerts
|

Challenge of Utilization Vegetal Extracts as Natural Plant Protection Products

Abstract: Natural plant protection products (known as biopesticides), derived from natural materials (plants, bacterial strains, and certain minerals) that can be used to control pests, are an alternative to plant protection chemicals (known as pesticides) due to certain advantages: less toxic to humans and the environment, no release/leaching of harmful residues, and usually much specific to the target pests. This review focuses on the systematization of information highlighting the main advantages related to the natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 62 publications
1
39
0
1
Order By: Relevance
“…This is following previous research Das et al, [24]; Klys et al, [25]; Fernando and Karunatne [27]; Abtew et al, [35] which reported that the repellency of insects of insecticides can still have an effect on 1 until 24 hours after application and after that time the effect will not be too high on repellency. This phenomenon is since insecticides can evaporate over time, thereby reducing their repellency to target insects, which is in this case are S.oryzae [36][37].…”
Section: Discussionmentioning
confidence: 99%
“…This is following previous research Das et al, [24]; Klys et al, [25]; Fernando and Karunatne [27]; Abtew et al, [35] which reported that the repellency of insects of insecticides can still have an effect on 1 until 24 hours after application and after that time the effect will not be too high on repellency. This phenomenon is since insecticides can evaporate over time, thereby reducing their repellency to target insects, which is in this case are S.oryzae [36][37].…”
Section: Discussionmentioning
confidence: 99%
“…The application of PPPs gained immense popularity due to their economic, rapid, and effective increment of crop yields and to the decrement of losses from many pests, diseases, and weeds (Pogǎcean and Gavrilescu, 2009;Oruonye and Okrikata, 2010;Pavlis et al, 2010;Labite et al, 2011;Berk et al, 2016;Suteu et al, 2020). However, their widespread usage caused an adverse effect on the environment and led to its quality deterioration, the initiation and intensification of deep soil degradation processes, air contamination, insect losses, exposure of non-target organisms to mixtures of toxic residues, insect/pathogen/weed resistance, and chronic negative effects on human and animal health (Koul et al, 2008;Pogǎcean and Gavrilescu, 2009;Zanellato et al, 2009;Oruonye and Okrikata, 2010;Pavlis et al, 2010;Bajpai et al, 2011;Ibáñez and Blázquez, 2018;Hassauer and Roosen, 2020;Suteu et al, 2020;Zioga et al, 2020). Moreover, pesticides can be immobilised in soil and affect its organic matter and composition of the microbial community (Jouini et al, 2020).…”
Section: Plant Extracts As Plant Protection Productsmentioning
confidence: 99%
“…Moreover, pesticides can be immobilised in soil and affect its organic matter and composition of the microbial community (Jouini et al, 2020). Another significant threat associated with the utilisation of this type of products is the contamination of food as well as groundwater, which safeness and quality are essential because it is widely used for domestic and agricultural purposes (Pavlis et al, 2010;Labite et al, 2011;Berk et al, 2016;Suciu et al, 2020;Suteu et al, 2020). The estimated annual usage of pesticides is 2.5 million tonnes while the damages caused by them reach $100 billion globally (Koul et al, 2008;Saroj et al, 2019).…”
Section: Plant Extracts As Plant Protection Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Essential oils (EOs) are mixtures of plant-derived secondary metabolites that are extensively applied in food preservation and medical practices for thousands of years (Majewska et al, 2019 ; Suteu et al, 2020 ; Giunti et al, 2021 ). Many aromatic plants are known for their extraordinary ability to produce a large amount of EOs that can repel grazers, kill pests, or inhibit the growth of competing plants growing in the neighborhood (Willmer et al, 2009 ; Aungtikun et al, 2021 ; Han et al, 2021 ; Sousa et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%